LEGAL SUPPORT OF THE MECHANISM OF THE QUALITY CONTROL OF HEALTHCARE SERVICES IN UKRAINE - Gavryliuk, A.O.; Zhаrlіnskа, R.G.; Mischuk, A.A. (World of Medicine and Biology, 2019)
The authors consider the main stages of the development of the health care quality (HCQ) provision in Ukraine: the state (budget) system of healthcare; the stage of the new economical mechanism introducing; the independence of the country with the appearance of market mechanisms of economics. The authors focus on legal support of mechanism of the quality control of healthcare services and analyze the legislation system in the field of state quality control. The article describes different ways of internal and external healthcare quality control: health care standardization, licensing, accreditation, self-rating of medical workers; expert rate; clinical audit; monitoring of the indicators quality system; certification. The article proposes ways of harmonization of the national legal framework and adaptation to the relevant norms of international law.
Keywords: health care quality; internal and external healthcare quality control